2015
DOI: 10.1007/s11250-015-0777-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein level and urea in concentrate mixture on feed intake and rumen fermentation in swamp buffaloes fed rice straw-based diet

Abstract: Four rumen-fistulated Thai native swamp buffaloes were randomly assigned according to a 2 × 2 factorial arrangement in a 4 × 4 Latin square design to assess the effect of protein (CP) level and urea (U) source in concentrate diet on feed utilization and rumen ecology. The treatments were as follows: concentrate containing CP at 120 g/kg (soybean meal, SBM) (T1), 160 g/kg (SBM) (T2), 120 g/kg (U) (T3), and 160 g/kg (U) (T4), respectively. All buffaloes were fed concentrate at 10 g/kg of body weight, and rice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…However, there was no different effect among each level of U and M supplement. Rumen fermentation and digestibility were increased with the increasing levels of U supplement, which could be due to the increased rate of rumen microorganisms growth resulting from the presence of more available N in the form of ammonia from the hydrolysis of U (Boucher et al 2007;Khattab et al 2013;Kang et al 2015). In addition, Wanapat, Kang, Khejornsart et al (2013) reported that the supplementation of U and M could increase rumen degradability of whole-crop rice silage.…”
Section: Resultsmentioning
confidence: 98%
“…However, there was no different effect among each level of U and M supplement. Rumen fermentation and digestibility were increased with the increasing levels of U supplement, which could be due to the increased rate of rumen microorganisms growth resulting from the presence of more available N in the form of ammonia from the hydrolysis of U (Boucher et al 2007;Khattab et al 2013;Kang et al 2015). In addition, Wanapat, Kang, Khejornsart et al (2013) reported that the supplementation of U and M could increase rumen degradability of whole-crop rice silage.…”
Section: Resultsmentioning
confidence: 98%
“…The true digestibility was increased regardless M dose (M0.5 = M1 = M2), and the NDF digestibility was the highest in M2 group. The lack of U influence on in vitro true and NDF digestibilities is rather surprising as it is supposed that rumen fermentation and digestibility increases with the U supplementation due to the increased rumen microorganisms growth rate as there is more available N in the form of ammonia from the urea hydrolysis (Khattab et al, 2013;Kang et al, 2015). Moreover, found that supplementation of U and M could increase rumen degradability of whole crop rice silage.…”
Section: Treatmentsmentioning
confidence: 99%
“…Similar to our results, Reddy and Reddy (1988) reported that dietary supplementation of energy and protein increased the digestibilities of nutrients in crossbred calves. Similarly, Kang et al (2015) reported increased digestibility of CP, NDF and ADF in buffaloes fed high protein diet. Khattab et al (2013) also observed significantly higher digestibility of DM, OM and CP in sheep with increasing dietary urea levels, which could be attributed to the increased growth rate of rumen microorganisms as more available N in form of ammonia from the hydrolysis of urea (Boucher et al 2007).…”
Section: Intake and Digestibility Of Nutrientsmentioning
confidence: 83%
“…Khattab et al (2013) also observed significantly higher digestibility of DM, OM and CP in sheep with increasing dietary urea levels, which could be attributed to the increased growth rate of rumen microorganisms as more available N in form of ammonia from the hydrolysis of urea (Boucher et al 2007). Furthermore, the dietary protein supplementation increases total tract digestibility in ruminants consuming lowquality forage (Kang et al 2015). Supplementing the CON diet with synchronous supply of both rapidly fermentable energy and rumen degradable protein through customised supplement had shown a positive associative effect on digestibility of DM by accelerating the growth of rumen microbes (Yulistiani et al 2015).…”
Section: Intake and Digestibility Of Nutrientsmentioning
confidence: 93%
See 1 more Smart Citation